POSSIBILITIES OF SURGICAL TREATMENT OF CICATRICAL STENOSIS OF THE TRACHEA - B. N. Kotiv; I. B. Popov (Вестник хирургии имени И.И. Грекова)
The treatment of cicatrical stenosis of the trachea was performed in 193 patients at the age 8–65 years (132 of men and 61 women). The length of cicatrical stenosis shaped mainly by growth of granulation tissue and its different combinations consisted of 0,5 to 2,5 cm, getting 3,0 cm and more in 74 cases. The peculiar features of such cicatrical changes were characterized differently depending on its dominating localization on the length of the trachea — in the area of the neck or in the range of the mediastinum. Respiratory distresses, which were the main clinical manifestation of the disease, depended on the degree of stenisis of the trachea opening with the cicatrical process in each case. The decrease of size of the trachea opening with respect to natural size on1/3 was considered as the first degree of stenosis, on2/3 — II degree, more than on2/3 — III degree. The efficiency of endoscopic methods of treatment was the most significant in cicatrical stenosis of trachea with the length not more than 0,5–1,5 сm and dramatically decreased with the increase of length. The cicatrical stenosis of trachea with the length more than 3,5–3,0 сm should be considered as the indication for radical surgical intervention such as resection and plasty of trachea with forming of intertracheal or laryngotracheal anastomosis.